TEACHING HERITAGE BOOKS TO IMPROVE READING SKILLS AT THE SALAFIYAH HAMIDIYYAH INSTITUTE IN BULUREJO-DIWEK-JOMBANG SCIENTIFIC RESEARCH - Muhamad Yusrur Roziq; Abdul Qadir; Arif Setiabudi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The background to this research is that although most students have followed the learning process, many are still unable to read the yellow book well. This indicates a gap between the methods used and the expected results, especially in mastering the skill of reading yellow books. The research problem is summarized in (1) What are the steps of teaching the book at the “Salafiyyah Hamidiyyah” Institute in Bolorejo-Dewek-Jombang? (2) How to improve reading skills at the “Salafiyyah Hamidiyyah” Institute in Bolorejo-Dewek-Jombang? The objectives of this research are: (1) To know the steps of teaching the book at the “Salafiyyah Hamidiyyah” Institute in Bolorejo-Dewek-Jombang, and (2) To know the improvement of reading skill in the "Salafiya Hamidiyya" Institute, Bolorijo-Dewik-Jombang. The research method used is the qualitative method of descriptive research type. Data collection techniques include observation, interviews and documentation.The research sample consisted of textbook teachers and first and second grade students. The research results showed that the process of learning the books takes place in stages, starting with introducing the letters of Hajj and dictation exercises, then introducing the basics of grammar and morphology through the “Yasarna” method, then moving on to learning the basic books such as Aqeedah al-Awam.The Ship of Success and the Forty Nuclear Hadiths. In the process of improving the ability to read books, two main methods are used: bandungan (reading and explanation by the teacher) and sorogan (direct reading by students in front of the teacher). In addition to the technical aspects, spiritual methods are also used.Such as reciting Surat Al-Fatihah and praying to the author of the book before beginning to study. Reading ability is assessed through three main aspects: reading fluency, the ability to analyze word forms (shaqawa), and understanding sentence structure (sentence).This teaching strategy has been proven to significantly improve students' reading skills, while promoting spiritual and moral values ​​in the learning process